Development of hybrid membrane (polysulfone and zeolites) for gas separation application - Siti Badriah, Harun (2010)
Objectives of this research are developing and fabricate hybrid membrane (polysulfone and zeolites) for gas application, in a way to increase the selectivity and permeability. To achieve this characteristics polymer, zeolites and coupling agent were used as material to produce this hybrid membrane. In the experiment, the membrane prepared at different zeolites and chloroform loading. The solution was stirred at 24 hours to get a homogenous solution. New coupling agent (a mix of formaldehyde and carboxylic acid) was used. After casting process, the membrane was tested by permeation cell to study the permeability and selectivity of the produced membrane. Several gases were used to test this membrane such as O2, N2, CH4 and CO2. The result was compared to original membrane which means the membrane not mix with zeolites. The permeability and selectivity values for 40% zeolites loading for gas CO2 and CO2/CH4 were 995 X 10-6 and 0.889. Results for O2 and O2/N2 were 732 X 10-6 and 0.660. For zeolites loading 12%, permeability and selectivity values for gas CO2 and CO2/CH4 were 595 X 10-6 and 0539. For O2 and O2/N2, the values were 947 X 10-6 and 1.008. Result obtained was not at the standard values due to incompatibility of new coupling agent used, and the pair of zeolitespolymer. To produce hybrid membrane, the parameter studied, the zeolites and polymer pair and the use appropriate of coupling agent are very important.